Nutritional assessment of children at the day care center “Marineritos del Sur” in Cienfuegos province, Cuba. - Zeida Bárbara Alejo Cruz; Gema Matienzo González Carvajal; Caridad Hernández Gutiérrez; Ernesto Martínez Ferrer (Medisur)
Background: In many countries in the last few years, there has been an increasing interest for the assessment of the Nutritional System which can be defined as a systemic and permanent process of collection, transmission analysis and interpretation of the information that allows to keep updated knowledge of the nutritional state. The follow up of the children´s growth and development has the importance not only to assist the children´s needs at a determined age but also to assist them with a preventive criteria taking into account their dynamic and changing characteristics. Objectives: To assess nutritionally the children gathered at the ages from 2 to 6 years that attend the day care center ¨Marineritos del Sur¨ for more than one year during the period September 1 st - March 2000. Methods: The variables under study were age, sex, weight, folds brachial circumference and past illnesses. Results: According to the indicators weight/size, size/age, weight / age, tricipital fold/ age, brachial circumference / age, patients between 10 and 90 percentile had a predominance. The calculus of the Z point showed that 67,66 % of the children were eutrophic, 27,=6 tended to obesity and 5,28 malnourished. Giardia Lambia was the most frequent isolated parasite.